PENGARUH CURRENT RATIO DAN QUICK RATIO TERHADAP PROFIT MARGIN PADA PT. INDOSAT, Tbk PERIODE 2005-20014 - Pupu Sopini (Universitas Batanghari Jambi, 2017)
This study aims to determine the development of the Current Ratio, Quick Ratio and its influence toward the Gross Profit margin on PT. Indosat, Tbk period 2005-2014. The method used is quantitative method with data processing using multiple linear regression statistical formula. Current Ratio progressing fluctuating tends to decrease with an average growth of 9.5%. Quick ratio fluctuates progressing tends to decrease with an average growth of 9.3%. Gross Profit Margin progressing fluctuating tends to decrease with an average growth of 20.1%. Current Ratio influences the direction toward the Gross Profit Margin. It means that any change current ratio of 1 percent, the Gross Profit Margin will increase by 4.543%. Quick Ratio has effected opposite toward the Gross Profit Margin. If any changes occur Quick Ratio of 1 percent, the gross profit margin will be decreased by 4.426%. The amount of the coefficient of determination of the regression results of two independent variables (Current Ratio and Quick Ratio) toward the gross profit margin amounted to 0,745, it means that the effect of variable Current Ratio and Quick Ratio of Gross Profit Margin at PT. Indosat Tbk is 74.5% and the remaining 25.5% is influenced by other variables. Keywords: Current Ratio, Quick Ratio, Profit Margin